Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1116/1.583653
|View full text |Cite
|
Sign up to set email alerts
|

Refractory metal nitride rectifying contacts on GaAs

Abstract: Articles you may be interested inPlasma-induced damage of GaAs during etching of refractory metal contacts Thermal stability and barrier height enhancement for refractory metal nitride contacts on GaAs Appl. Phys. Lett. 50, 445 (1987); 10.1063/1.98169Refractory metal contacts to GaAs: Interface chemistry and Schottky-barrier formationThe electrical characteristics of reactive-sputtered refractory metal nitride contacts on GaAs are investigated for their high-temperature stability after rapid-thermal annealed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several groups approached the preparation of group 4 transition metal nitrides, in particular with titanium and zirconium. TiN and ZrN are important for several applications: hard protective coatings; diffusion barrier in integrated circuit devices; , gate materials; thin-film thermistors; Josephson junctions; decorative optical coatings …”
Section: Introductionmentioning
confidence: 99%
“…Several groups approached the preparation of group 4 transition metal nitrides, in particular with titanium and zirconium. TiN and ZrN are important for several applications: hard protective coatings; diffusion barrier in integrated circuit devices; , gate materials; thin-film thermistors; Josephson junctions; decorative optical coatings …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and structure of dinuclear niobium and titanium complexes bearing a cyclopentadienyl-propylimide ligand were previously reported by Green and Mountford. 18 We decided to exploit the known (2,3,4,5-tetramethylcyclopenta-1,4-dienyl)-1-ethanamine (1) as a supporting ligand and initially attempted metalation of 1 with Zr(NMe 2 ) 4 . After several examinations, we found that the Zr 3 imido complex 2 could be obtained from the endo-diene isomers of 1 (including the exo isomer <5%) in a moderate yield (Scheme 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Zirconium nitride (ZrN) thin films have many applications deriving from their unique properties such as hard protecting coatings, diffusion barriers, gate materials, and Josephson junctions . A variety of deposition techniques for ZrN thin films have been developed using certain zirconium precursors with NH 3 , H 2 /N 2 , or the forming gas plasma. Among the precursors Zr­(NMe 2 ) 4 is the most representative, enabling mild and pinhole-free film growth.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray quality crystals were obtained by storing a concentrated THF solution at −40 °C for 48 h. Mp is not observed (dec). 1 Synthesis of ( t BuN)VCl 3 (DAD) (6). ( t BuN)VCl 3 (2.044 g, 8.948 mmol) was added to a solution of 1,4-di-tert-butyl-1,3-diazabutadiene (1.656 g, 9.843 mmol) in 100 mL of THF.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Specifically, alloys of the metals have applications in aerospace and nuclear materials, coatings for hardening tools and corrosion protection, and integrated circuits. 1−4 Refractory metal nitrides have been used to make protective and biocompatible coatings, 5 transistor contacts and electrodes, 6,7 copper−silicon diffusion barriers in integrated circuits, 8−13 Schottky diode contacts, 14 cathodes in lithium ion batteries, 15 and plasmonic materials 16 and have been used in catalysis. 17−20 A reliable method for preparing thin films of refractory metals and their nitrides is chemical vapor deposition (CVD).…”
Section: ■ Introductionmentioning
confidence: 99%